Pengaruh Pendidikan dan Beban Kerja terhadap Kompensasi serta Dampaknya terhadap Kinerja Tenaga Fasilitator Lapangan pada Satuan Kerja Penyediaan Perumahan Provinsi Jambi - Sunarti, Sunarti; Yamali, Fakhrul Rozi; Sudirman, Sudirman (J-MAS (Jurnal Manajemen dan Sains), 2024)
The purpose of this study is to describe the TFL performance, workload, compensation, and education in the Jambi Province Housing Provision Working Unit. It also seeks to ascertain and evaluate the impact of workload, compensation, and education on TFL performance in the Jambi Province Housing Provision Working Unit. Both quantitative and descriptive approaches of verification were employed in this study. A saturation or census sampling technique was used to determine the study's sample. The study's sample is the full TFL population in 2022, which is limited to 63 people. The path analysis method is used in this study. Employee education at the Jambi Province Housing Provision Work Unit is described as belonging to the "Appropriate" category, workload is in the "Very High" category, work environment is in the "good" category, employee compensation is in the "High" category, and performance is in the "Very High" category. The Jambi Province Housing Provision Work Unit's TFL is classified as "Good." The path analysis's findings, which show that education has a 21.8% impact on performance through compensation, and that the impact of education on workload and compensation is 9.7%, with a total effect of 31.5%. This chart illustrates how education through compensation increased the TFL Performance of the Housing Provision Work Unit in the Province of Jambi by 31.5%. Workload has a 25.3% impact on performance through compensation; it has a 9% impact on performance through education and compensation; the overall effect is 34.3%. Reducing the Workload via Compensation contributed 34.3% to the TFL Performance of the Housing Provision Work Unit in the Province of Jambi. The combined impact of education and workload through compensation has a direct effect on performance of 47.1%, an indirect effect of 186%, and a total effect of 65.8%. This figure illustrates how these factors affected the performance of Jambi Province Housing Provision Work Unit employees by 65.8%.